Predicting and Preventing Epilepsy in Sturge-Weber Syndrome? - Csaba Juhász (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the University of Montreal studied potential predictors of epilepsy in young patients with Sturge-Weber syndrome (SWS).